Association between chronic obstructive pulmonary disease and cardiovascular disease in adults aged 40 years and above: data from NHANES 2013–2018 - Chen, Hong; Luo, Xiaojia; Du, Yuejun; He, Chenyun; Lu, Yanjun; Shi, Zixuan; Zhou, Jin (BMC pulmonary medicine, 2023)
Background Chronic obstructive pulmonary disease (COPD) and cardiovascular disease (CVD) are two major age-related diseases prevalent in the elderly. However, it is unclear whether there is a higher prevalence of one or more CVDs in COPD patients compared to those without COPD, and the magnitude of this increased prevalence. Methods This population-based cross-sectional study was conducted using data from the National Health and Nutrition Examination Survey (NHANES) 2013-2018 among American adults aged 40 years and above. Multivariable logistic regression models (including unadjusted model, minimally adjusted model, and fully adjusted model) were conducted to investigate the association between COPD and the prevalence of one or more CVDs, including coronary heart disease, heart failure, angina pectoris, heart attack, diabetes, and stroke. Results This study included 11,425 participants, consisting of 661 participants with COPD and 10,764 participants without COPD. COPD patients had a significantly higher prevalence of CVD than those without COPD (59.6% vs. 28.4%). After adjusting for covariates, COPD was significantly associated with the prevalence of one CVD (OR = 2.2, 95% CI = 1.6-3.0, p < 0.001), two or more CVDs (OR = 3.3, 95% CI = 2.2-5.0, p < 0.001), and three or more CVDs (OR = 4.3, 95% CI = 2.9-6.5, p < 0.001). Conclusions Patients with COPD have a higher prevalence of one or more CVDs compared with those without COPD. Our findings highlight the importance of CVD prevention and management in patients with COPD. Keywords: Chronic obstructive pulmonary disease (COPD), Cardiovascular disease (CVD), NHANES, Aging